The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/imb.12747
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and quantification of cryptochrome expression in the brain of the pea aphid Acyrthosiphon pisum

Abstract: Aphids are paradigmatic photoperiodic animals often used to study the role of the circadian clock in the seasonal response. Previously, we described some elements of the circadian clock core (genes period and timeless) and output (melatonin, AANATs and PTTH) that could have a role in the regulation of the aphid seasonal response. More recently, we identified two opsins (C-ops and SWO4) as candidate input photoperiodic receptors.In the present report, we focus on the study of cryptochromes (cry) as photorecepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Hence, HaTim's diel expression in H. armigera larval head can easily be dampened under constant conditions, as observed in some other insect species. 16,[50][51][52] Under a short-day-length photoperiod, the phase of the HaTim expression rhythms was advanced (Fig. S2(C,D)).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, HaTim's diel expression in H. armigera larval head can easily be dampened under constant conditions, as observed in some other insect species. 16,[50][51][52] Under a short-day-length photoperiod, the phase of the HaTim expression rhythms was advanced (Fig. S2(C,D)).…”
Section: Discussionmentioning
confidence: 99%
“…We may speculate that whatever is the selection pressure that drove the divergent evolution of core clock proteins PER and TIM it might have also similarly driven the evolution of the divergent clock neuropeptide PDF. The fact that the levels of period gene transcription, similar to the PDF-coding gene, are significantly influenced by the photoperiod (with SDs inducing higher expression of both genes) speaks for this hypothesis [ 69 , 71 ]. Thus, it is possible that the function of particular clock genes (including PDF) has been directed towards photoperiod-related tasks at the expense of circadian clock ones.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, compound eyes do not appear to play a role as photoreceptors for photoperiodic responses in aphids [ 88 ], which may explain the absence of dendritic PDF fibres in AME. Instead, the photoperiodic photoreceptor of aphids was localized to the lateral superior protocerebrum [ 88 ], where CRY1-positive clock neurons were later found [ 30 , 69 ]. There, the fibres of these CRY1-positive clock neurons intermingle with fibres of the PDF neurons making it likely that the photosensitive CRY1 not only synchronizes the circadian clock of aphids but at the same time transfers information about day length (photoperiod) to the PDF-positive clock neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the photoperiodic cue is perceived in heads [ 23 , 24 ] and then transduced to the embryos presumably via the neuro-endocrine and hormonal system [ 25 , 26 ]. More targeted analyses revealed the differential expression upon photoperiod shortening of photoreceptors [ 27 , 28 ], circadian clock [ 29 ], melatonin [ 30 , 31 ] and insulin [ 32 ] genes. These data suggest a role for these pathways in the early steps of the photoperiodic cue perception and transduction.…”
Section: Introductionmentioning
confidence: 99%